Evaluation of a Learning Collaborative to Implement Postgraduate Nurse Practitioner (NP) and/or Physician Associate (PA) Residency or Fellowship Programs in a Community Health Center - Meaghan Angers; Manjari Mishra; Amanda Schiessl; Margaret Flinter; Nicole Seagriff; Kerry Bamrick; Charise Corsino; May Oo (Journal of Primary Care & Community Health)
This paper presents findings from a study focused on establishing Postgraduate Nurse Practitioner (NP) and/or Physician Assistant (PA) Training Programs within federally funded health centers and look-alikes. The study aimed to identify facilitators and barriers encountered by participating health centers in the Health Resources and Services Administration (HRSA) funded Postgraduate NP and/or PA Training Programs Learning Collaborative. Of the 78 health centers that participated in the learning collaborative since 2016, 47.44% (n = 37) responded to the survey. The top facilitators for launching a program were leadership support, clinical support, and dedicated time for planning and implementation. The top barriers for not launching a program were lack of financial resources, competing priorities, and limited dedicated time for planning and implementation. Interviews echoed these findings, as well as highlighted additional facilitators of grant funding and mission-driven workforce pathway planning. Survey results from those that launched a training program revealed that 215 graduates have completed the program, with 86 employed within the health center. These findings provide valuable insights and guidance to support health centers in their journey towards building and launching a Postgraduate NP and/or PA Training Program, as well as informing future HRSA policies, programs, and funding.